2011
DOI: 10.1149/2.052201jes
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of ALD-HfO2/GaAs Pretreated with Trimethylaluminium

Abstract: The simultaneous self-cleaning and passivation of an as-received GaAs substrate using trimethylaluminium (TMA) pretreatment before the atomic layer deposition (ALD) of HfO 2 was systematically investigated. The change of the interfacial characteristics was probed as a function of the number of treatment cycles and the post-deposition annealing temperature and related with various electrical properties of the HfO 2 film. The TMA pretreatment removed the Ga-and As-oxides more effectively than the ALD-HfO 2 proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Moreover, Ge oxide easily grows on Ge surface exposed to air for a very short time, even after chemical pretreatment with HF or HCl [11] .In recent years, it has been demonstrated that the native oxide on Ш-V semiconductors (GaAs, InSb, etc. ), InGaAs and Ge surfaces could be effectively "cleaned" through a ligand exchange mechanism between the atomic layer deposion (ALD) precursor and the interfacial native oxide [12][13][14][15][16][17][18] . For example, Al2O3 precursor -trimethylaluminum (TMA) can effectively minimize Ga and As oxides by the formation of volatile products such as AsCH and As[OCH(CH3)2]3 followed ligand exchange mechanism [12,13] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Ge oxide easily grows on Ge surface exposed to air for a very short time, even after chemical pretreatment with HF or HCl [11] .In recent years, it has been demonstrated that the native oxide on Ш-V semiconductors (GaAs, InSb, etc. ), InGaAs and Ge surfaces could be effectively "cleaned" through a ligand exchange mechanism between the atomic layer deposion (ALD) precursor and the interfacial native oxide [12][13][14][15][16][17][18] . For example, Al2O3 precursor -trimethylaluminum (TMA) can effectively minimize Ga and As oxides by the formation of volatile products such as AsCH and As[OCH(CH3)2]3 followed ligand exchange mechanism [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…), InGaAs and Ge surfaces could be effectively "cleaned" through a ligand exchange mechanism between the atomic layer deposion (ALD) precursor and the interfacial native oxide [12][13][14][15][16][17][18] . For example, Al2O3 precursor -trimethylaluminum (TMA) can effectively minimize Ga and As oxides by the formation of volatile products such as AsCH and As[OCH(CH3)2]3 followed ligand exchange mechanism [12,13] . And it achieves the effects of removal of thermal unstable oxide on GaAs surface and improvement of interface quality [12,13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from a basic research perspective there are several conflicting results that have created confusion as to the exact nature of the so-called "interface clean-up" reaction. For example, it was proven that native oxide removal through reactions with TMA was a first-contact effect [5,[16][17][18][19][20][21]. But for ALD processes that used alkylamine precursors the well-documented continuous removal of the III-V surface native oxides even after the surface had been covered with 2 nm or more of the growing film hinted at the existence of a more complex reaction mechanism [4,9,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose we studied the interaction of the two types of precursors, alkyl-and alkyl amine, through an extended process temperature range from 200-300°C on native oxide-covered InAs(100) and GaAs(100). Most studies for the ALD of Al 2 O 3 on III-V compounds have been carried out at process temperatures of 300°C or above [5,[16][17][18][19][20][21]. The effectiveness of TMA at lower temperatures has been examined in only a few studies and, for the most part, these studies used substrates that were etched prior to deposition leaving only traces of the native oxides [19,29,30].…”
Section: Introductionmentioning
confidence: 99%